1986
DOI: 10.1007/bf00608214
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of codeine and its metabolite, morphine, after single and repeated oral administration

Abstract: Plasma concentrations of codeine and its demethylated metabolite, morphine, were determined after single and repeated oral administration of codeine. Twelve healthy volunteers received two doses of codeine 60 mg, 2.8 h apart. In order to achieve steady-state conditions codeine 60 mg was then taken every 8 h for a further five doses. The plasma concentrations of codeine and morphine after the first, second and seventh doses were analyzed by GC-MS. The maximum plasma concentrations of codeine and morphine were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 10 publications
8
34
0
1
Order By: Relevance
“…12). After oral administration, the exposure to codeine is almost 40-fold greater than that of morphine (Quiding et al, 1986). However, the potency of morphine at the m-opioid receptor is 600-fold greater (Volpe et al, 2011), thus the pharmacological effects of codeine administration are almost exclusively attributable to the active metabolite morphine (and its subsequent pharmacologically active glucuronide metabolites; see Section IV.B.15.).…”
Section: A Drugs With Active Metabolites That Dominate the Activitymentioning
confidence: 99%
“…12). After oral administration, the exposure to codeine is almost 40-fold greater than that of morphine (Quiding et al, 1986). However, the potency of morphine at the m-opioid receptor is 600-fold greater (Volpe et al, 2011), thus the pharmacological effects of codeine administration are almost exclusively attributable to the active metabolite morphine (and its subsequent pharmacologically active glucuronide metabolites; see Section IV.B.15.).…”
Section: A Drugs With Active Metabolites That Dominate the Activitymentioning
confidence: 99%
“…Although codeine has been widely used for about 150 years, its pharmacokinetics in man have been investigated mainly during the last 10 years (Guay et al, 1987;Findlay et al, 1977Findlay et al, , 1978Findlay et al, , 1986Quiding et al, 1986;Rogers et al, 1982). In two studies (Guay et al, 1987;Quiding et al, 1986) the plasma concentrations of codeine and its O-demethylated metabolite morphine were determined after single and repeated oral administration in healthy adult volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…In two studies (Guay et al, 1987;Quiding et al, 1986) the plasma concentrations of codeine and its O-demethylated metabolite morphine were determined after single and repeated oral administration in healthy adult volunteers. The hypothesis that codeine acts through biotransformation to morphine was proposed over 40 years ago (Sanfilippo, 1948).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have clinical implications because these compounds appear to have analgesic activity in both animals and man. In fact, it has been suggested that codeine exerts its analgesic effect by transformation to M (Sanfilippo, 1948) but other hypotheses exist (Quiding et al, 1986). NM is also considered to be an active metabolite of codeine and M, being approximately onefourth as potent as M in relieving postoperative pain (Lasagna & Komfeld, 1958).…”
mentioning
confidence: 99%